Photonic Devices: Plasmonic Metasurfaces for Switchable Photonic Spin–Orbit Interactions Based on Phase Change Materials (Adv. Sci. 10/2018). Issue 10 (17th October 2018) - Zhang, Ming; Pu, Mingbo; Zhang, Fei; Guo, Yinghui; He, Qiong; Ma, Xiaoliang; Huang, Yijia; Li, Xiong; Yu, Honglin; Luo, Xiangang
Abstract : Metasurfaces with switchable spin–orbit interactions (SOIs) offer an appealing platform for dynamic and reconfigurable beam manipulation. In article number1800835, Xiangang Luo and co‐workers demonstrate switchable SOIs experimentally via the combination of plasmonic metasurfaces with phase change materials (PCMs). The metadevices with switchable SOIs provide a promising route to achieve reconfigurable applications such as encrypted optical communications and dynamic holographic displays.